2021
DOI: 10.3390/ma14247759
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Materials for the Enrichment of Biogas with Methane

Abstract: Carbonaceous adsorbents have been pointed out as promising adsorbents for the recovery of methane from its mixture with carbon dioxide, including biogas. This is because of the fact that CO2 is more strongly adsorbed and also diffuses faster compared to methane in these materials. Therefore, the present study aimed to test alternative carbonaceous materials for the gas separation process with the purpose of enriching biogas in biomethane and to compare them with the commercial one. Among them was coconut shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The higher inflow rates of 10 L/min and 15 L/min ensured the methane content in upgraded biogas at the level of 87.4% and 84.3%, respectively. Bałys et al [55] conducted breakthrough experiments using sorbents derived from bio-waste materials for biogas upgrading. They found that coconut shell activated carbon as the sorbent ensured the purity of biogas initially containing 25 v% CH 4 and 75 v% CO 2 on the level of above 95 v% CH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The higher inflow rates of 10 L/min and 15 L/min ensured the methane content in upgraded biogas at the level of 87.4% and 84.3%, respectively. Bałys et al [55] conducted breakthrough experiments using sorbents derived from bio-waste materials for biogas upgrading. They found that coconut shell activated carbon as the sorbent ensured the purity of biogas initially containing 25 v% CH 4 and 75 v% CO 2 on the level of above 95 v% CH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The study presented in this article develops the ideas of the concept of sustainable environmentally friendly concrete, which implies the partial and complete replacement of the mineral components of concrete with natural and rapidly renewable analogues. Replacing large-mineral aggregate with walnut shells will partially eliminate complex mechanized and energy-intensive production processes associated with high greenhouse-gas emissions [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. At the same time, it is important to find a balance between the strength and density of the resulting composite, so that a decrease in the SC of the material is accompanied by a commensurate decrease in the density of the material.…”
Section: Introductionmentioning
confidence: 99%